Seismic Performance Evaluation and Retrofit of Liquid Storage Tanks- Case Study - Bülent Erkmen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Seismic performance of existing liquid pentane storage tanks located in a tank farm in Turkey Kocaeli region, which is a high seismic region, is studied. The tanks are free-to-slide on their existing reinforced concrete foundation. The tanks seismic performance is evaluated based on the 2018-Turkish Building Seismic Code and API 650 provisions using three-dimensional (3D) finite element methods with nonlinear time-history analysis. The developed FE model for seismic performance assessment of the existing tanks includes tank-foundation dynamic interaction, tank supports uplifting, and sliding over the foundation. The study revealed poor and inadequate seismic performance for the existing tanks due to lack of tank foundation-anchorage. A practical seismic retrofit strategy is developed to anchor the tanks to the existing reinforced concrete foundation. Prefabricated and field-welding free steel split sleeves are developed for the tank anchorage. The retrofitted tank seismic performance is evaluated to verify the proposed retrofit strategy and its effects on tank seismic behavior. The base shear and uplift reactions for the retrofitted tank are monitored for the anchorage design. Tank top drift, which is an important seismic performance parameter for tank piping, and tank steel material yielding are also checked to verify adequacy of the proposed retrofit strategy.